Gender, city, and violence(s). Emerging territorialities and cartographies (REVISTA NODO, 2020)
Two paradoxical processes concur in the cities of Latin America before the neoliberal advance in the region: on the one hand, the violence that is expressed particularly on the body of women and the dissident bodies and on the other, the expressions of emerging subjects, in particular of movement of women, in the public space. The present work investigates the relations between the symbolic-representative and material physical dimensions of gender constructions and violence(s) in the public space of the city. The analysis of initiatives in the metropolitan area of Tucumán is incorporated. The results presented come from a work strategy developed in a space of university experimentation of gender and urban planning. Methodological approaches to urban planning, anthropology, geography are used. In particular, social cartography is adopted as an interpretive tool and instrument for action for the right to the city.
Keywords: inequalities; public space; gender; city